Long-Term Effects of Childhood Nutrition: Evidence from a School Lunch Reform - Lundborg, Petter; Rooth, Dan-Olof; Alex-Petersen, Jesper (Review of Economic Studies, 2022)
Abstract We study the long-term impact of a policy-driven change in childhood nutrition. For this purpose, we evaluate a program that rolled out nutritious school lunches free of charge to all pupils in Swedish primary schools between 1959 and 1969. We estimate the impact of the program on children’s economic, educational, and health outcomes throughout life. Our results show that the school lunch program generated substantial long-term benefits, where pupils exposed to the program during their entire primary school period have 3% higher lifetime income. The effect was greater for pupils that were exposed at earlier ages and for pupils from poor households, suggesting that the program reduced socioeconomic inequalities in adulthood. Exposure to the program also had substantial effects on educational attainment and health, which can explain a large part of the effect of the program on lifetime income.